CD4+CD25+CD127low regulatory T cells play predominant anti-tumor suppressive role in hepatitis B virus associated hepatocellular carcinoma - Sharma, Shreya; Khosla, Ritu; David, Paul; Rastogi, Archana; Vyas, Ashish; Singh, Dileep; Bhardwaj, Ankit; Sahney, Amrish; Maiwall, Rakhi; Sarin, Shiv K.; Trehanpati, Nirupma (Frontiers in Immunology, 2015)
Background: Hepatocellular carcinoma (HCC) is the second leading cause of cancer death worldwide and hepatitis B is one of the commonest causes. T regulatory cells (Tregs) are strong immunomodulators and are likely to play a major role in HCC development. HBV infection is reported to induce expansion of Tregs. We investigated the CD4+CD25+CD127−veFoxP3+ Tregs in HBV-related HCC as compared to non-HBV-HCC. Patients and Methods: Whole blood immunophenotyping was analyzed by multicolor flow cytometry in patients with HBV-related HCC (HBV-HCC, n = 17), non-HBV-HCC (n = 22; NASH = 16, alcohol-related = 6), and chronic hepatitis B infection (CHBV; n = 10). Tregs functionality was checked by in vitro suppression assays using CD4+ CD25+ CD127low Tregs. Levels of serum alpha-fetoprotein (AFP), expression of FoxP3, IL-10, PD1, TGF-β, and Notch in Tregs, and liver explants were analyzed by flow cytometry, immunohistochemistry, and quantitative RT-PCR. Results: CD4+CD25+hi and Foxp3 expression in CD4+CD25+hiCD127low was significantly increased (P = 0.04, P = 0.007) in HBVHCC compared to non-HBVHCC and CHBV patients. HBVHCC also showed high IL-10 and TGF-β secreting CD4 + CD25 + hiTregs. The PD1 expression in CD4 + CD25+hi was significantly decreased in the HBVHCC than non-HBVHCC. In HBVHCC, AFP levels were significantly high (median 941, range 2–727940) than non-HBVHCC (median 13.5, range 2–18,900). In HBVHCC, patients with high AFP (range; 3982–727940 ng/ml) showed positive correlation with Foxp3 expression in CD4+CD25+hi CD127low (r = 0.857, P = 0.014). Reduced PD1 expression in HBVHCC also had negative correlation with FOXP3 in CD4+CD25+hi CD127low (r = −0.78, P = 0.04). However, AFP levels in non-HBVHCC showed negative correlation with (R = −0.67, P = 0.005) with CD4+CD25+hi Tregs. Conclusion: Our results demonstrate that CD4+ CD25+hi Tregs from HBVHCC patients have decreased expression of PD1, resulting in higher IL-10 and TGF-β secretion. Increased suppressive ability of Tregs in HBV-related HCC confers increased anti-tumor suppressive response than in non-HBV-HCC. Modulation of Tregs and PD1 may serve as useful therapeutic targets.